Protecting Indigenous Hunters: The Social and Environmental Protection Regime in the James Bay and Northern Quebec Land Claims Agreement. - Feit, Harvey A. (University of Michigan, Natural Resources Sociology, Monograph Series, 1982)
Cree and Inuit Peoples in northern Quebec recently negotiated the creation of a regional environmental and social protection regime as a part of their aboriginal rights agreement. This is an important first test of this way of giving local land-based Indigenous communities more effective voice in the regulation of development activities in their regions. In this chapter I briefly outline the context in which the James Bay and Northern Quebec negotiations took place and describe the form and logic of the social and environmental regime which was negotiated. I then evaluate the initial experiences with the regime. The question of how to design effective regimes has received considerably less attention than how to use legislation that already exists. This analysis addresses the former. I emphasize the need for: recourse against government abuses or omissions of laws and their application; ongoing monitoring of government policy and legislation; special means for Native participation; means of making inputs to decision-making effective; and the integration of social-environmental regimes with other protections for Native interests. In particular, I highlight the close link that must exist between the legal recognition of specific Native rights and any effective indigenous participation in the structures and processes for regulating regional development activities. I emphasize possible types of rights, structures and procedures which could be effective in the frequent cases where leverage is insufficient to gain recognition of an absolute Indigenous right to unilaterally regulate development activity in a region.
The author worked as an advisor to James Bay Cree organizations from 1972 during their court case against a hydro-electric project, and the negotiations and initial implementation of the James Bay and Northern Quebec Agreement and treaty. During the initial implementation of the Agreement, from 1976 to 1981, he assisted the Cree Regional Authority and was a CRA appointee on two of the boards set up to administer the provisions of the social and environmental protection regime.
Keywords: Social Impact Assessment; Environmental Protection; Resource Development; Indigenous Peoples; Monitoring Government Actions; Local Resource Management; James Bay and Northern Quebec Agreement